2017
DOI: 10.1080/09540105.2017.1326469
|View full text |Cite
|
Sign up to set email alerts
|

Development of an immunochromatographic assay for the detection of alternariol in cereal and fruit juice samples

Abstract: An immunochromatographic strip was developed for the determination of alternariol (AOH) using both semi-quantitative and quantitative methods based on a sensitive monoclonal antibody we produced. With AOH-spiked samples, the visual limit of detection for cereal and juice were 160 ng/g and 25 ng/mL, and the cut-off values were 640 ng/g and 100 ng/mL, respectively. For quantitative analysis based on a strip scan reader, the calculated limit of detection was 15.5-19.4 ng/g for cereal and 2.8-3.5 ng/mL for fruit j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The first antibodies and immunoassays for AOH were reported in 2011 [10,11]. Since then, a few immunoassays have been described using either polyclonal or monoclonal antibodies specific to AOH [12,13], and only one study has been published using an antibody specific to AME [14]. Additionally, Wang et al have reported a generic antibody for both mycotoxins [15].…”
Section: Introductionmentioning
confidence: 99%
“…The first antibodies and immunoassays for AOH were reported in 2011 [10,11]. Since then, a few immunoassays have been described using either polyclonal or monoclonal antibodies specific to AOH [12,13], and only one study has been published using an antibody specific to AME [14]. Additionally, Wang et al have reported a generic antibody for both mycotoxins [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is because a pH that is too high or too low will affect the physical and chemical properties of antigens and antibodies. 16 The results of optimization are revealed in Figure 4 A. From the test results, the pH value was in the range of 4.0–8.6, the antibody titer was basically unchanged, and the highest IC 50 value was at pH 7.4, so pH 7.4 was selected.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters such as the quantity of gold-nanoparticle-labeled monoclonal antibody and the coating antigen, as well as the suspension buffer, have a certain influence on the analytical performance and sensitivity of a lateral-flow ICA strip. 16 Each condition was analyzed with a negative sample (0 ng/mL DAS) and a positive sample (25 ng/mL DAS).…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, liquid chromatography–tandem mass spectrometry (LC-MS/MS) ( Krausová et al, 2021 ), immunoassay ( Ackermann et al, 2011 ; Burkin and Kononenko, 2011 ; Kong et al, 2017 ; Man et al, 2017 ; Singh et al, 2018 ; Wang et al, 2018 ; Cai et al, 2021 ; Liang et al, 2021 ) and other methods with molecularly imprinted polymer or aptamers as core reagents were used to detect Alternaria mycotoxins in food and biology samples ( Quílez-Alburquerque et al, 2021 ; Wang et al, 2022 ). Given the advantages of simple operation, less time consumption, and low cost, immunological methods were considered to be the most suitable method for the on-site detection of Alternaria mycotoxins in food samples ( Ackermann et al, 2011 ), and an antibody was supposed to be the most important reagent.…”
Section: Introductionmentioning
confidence: 99%